Differences in analgesic use in community‐dwelling persons with and without Alzheimer's disease. (14th November 2016) - Hamina, A.; Taipale, H.; Tanskanen, A.; Tolppanen, A.‐M.; Tiihonen, J.; Hartikainen, S.
Abstract: Background: There are conflicting findings about analgesic use among persons with cognitive impairment compared to cognitively intact older persons. The objective of our study was to investigate the prevalence of analgesic use in community‐dwelling persons with and without Alzheimer's disease (AD), within six months after AD diagnosis and to find out factors associated with the use of analgesics and specific analgesic groups. Method: We utilized data from register based MEDALZ (Medication use and Alzheimer's disease) cohort consisting of all community‐dwelling persons diagnosed with AD during 2005–2011 in Finland and their matched comparison persons without AD. Altogether, 67, 215 persons with AD and one comparison person for each case were included. Drug use data were collected from the Prescription Register and comorbidities from Special Reimbursement and Hospital Discharge Registers. Results: Statistically significant ( p  < 0.001) yet mostly small differences were found for analgesics use: analgesics were used by 34.9% and 33.5% of persons with and without AD, respectively. Paracetamol was the most frequently used analgesic both among persons with (25.0%) and without AD (19.1%). Persons with AD used less frequently NSAIDs (Nonsteroidal Anti‐inflammatory Drugs) (13.2% vs. 17.3%) and mild opioids (5.0% vs. 7.1%), while the use of strong opioids was more common in comparison to persons without AD (1.3% vs. 1.1%, respectively). Analgesic users were more likely women, aged ≥80 years, had asthma/COPD, cardiovascular disease, diabetes, cancer, hip fracture, osteoporosis, rheumatoid arthritis, and lower socioeconomic position. Conclusion: Further studies are needed to evaluate the adequateness of pain relief in older persons with and without AD. Significance: Persons with Alzheimer's disease (AD) used more frequently paracetamol and less frequently NSAIDs and mild opioids. A decreasing trend of NSAID use was observed among persons with AD during the study period.